Faktor – Faktor yang Berhubungan dengan Pelaksanaan Inisiasi Menyusu Dini (IMD) Pada Ibu Primigravida di Klinik Pratama Mariana Medan - Nababan, Tiarnida; Gulo, Natalia Nur Iman; Islamiyah, Nurdini; Nurhaliza, Nurhaliza; Nurhasanah, Nurhasanah; Nurhidayati, Nurhidayati (Universitas Malahayati, 2024)
ABSTRACT Early Initiation of Breastfeeding (IMD) is a breastfeeding behavior in babies right after delivery, during when the infant is permitted to discover the nipple his mother's milk independently. IMD is carried out by the infant lies face down on mom's chest, allowing the mother's skin and baby touches each other for at least 1 hour after birth. Finding elements associated with the treatment of early breastfeeding initiation (IMD) is the goal of this study for Primigravida Mothers at the Pratama Mariana Clinic in Medan in 2023. This kind of research employs Chi Square testing and a cross-sectional approach in an analytic manner. The population in this study was primigravida mothers who visited the Pratama Mariana Medan Clinic in 2023, a total of 15 respondents and the method for collecting samples was Total Sampling. The results of univariate analysis showed that mothers had sufficient knowledge (53.3%), had low education (80%), were supportive (53.3%), and did not apply Early Breastfeeding Initiation (IMD) (66.7%). The results of bivariate assessment indicates a connection among maternal understanding and the application of IMD (p-value= 0.016), there is a connection among maternal education and the application of Early Breastfeeding Initiation (IMD) (p-value= 0.022), there is a relationship between support from the partner with Early Breastfeeding Initiation (IMD) management (p-value= 0.026). The study's findings showed that there is a connection among understanding, education and partner support and the management of IMD. Suggestions for health workers at the Pratama Mariana Clinic in Medan in 2023 are expected to increase health counseling and education regarding Early Breastfeeding Initiation (IMD) for Primigravida mothers during pregnancy so that IMD in babies is achieved. Keywords: Early Breastfeeding Initiation (IMD), Knowledge, Husband's Education and Support ABSTRAK Inisiasi Menyusu Dini (IMD) merupakan perilaku menyusui pada bayi segera sesudah dilahirkan yang mana bayi dibiarkan untuk menemukan putting susu ibunya dengan mandiri. IMD dilaksanakan dengan cara menaruh bayi di posisi telungkup di dada ibu agar kulit ibu serta bayi saling menyentuh setidaknya 1 jam sehabis dilahirkan. Tujuan studi ini yakni guna mengidentifikasi aspek-aspek yang berkaitan dengan tata laksana Inisiasi Menyusu Dini (IMD) Pada Ibu Primigravida Di Klinik Pratama Mariana Medan Tahun 2023. Tipe studi ini yakni studi analitik menggunakan desain cross sectional serta pengujian Chi Square. Populasi pada studi ini yakni ibu primigravida yang bekunjung di Klinik Pratama Mariana Medan Tahun 2023 sejumlah 15 responden serta metode untuk mengumpulkan sampel yakni Total Sampling. Hasil analisis univariat menunjukkan ibu berpengetahuan cukup (53,3%), pendidikan rendah (80%), mendukung (53,3%), tidak menjalankan Inisiasi Menyusu Dini (IMD) (66,7%). Hasil analisis bivariat menunjukkan adanya relasi diantara pemahaman ibu dengan pelaksanaan Inisiasi Menyusu Dini (IMD) (p-value= 0,016), adanya relasi diantara edukasi ibu dengan pelaksanaan Inisiasi Menyusu Dini (IMD) (p-value= 0,022), adanya relasi diantara support dari pasangan dengan tata laksana Inisiasi Menyusu Dini (IMD) (p-value= 0,026). Dari hasil studi bisa diambil simpulan bahwasanya ada relasi diantara pengetahuan, pendidikan serta support pasangan dengan tata laksana Inisiasi Menyusu Dini (IMD). Saran bagi tenaga kesehatan di Klinik Pratama Mariana Medan Tahun 2023 diharapkan agar meningkatkan penyuluhan dan edukasi medis tentang pemberian Menyusu Dini (IMD) pada ibu Primigravida selama kehamilan supaya IMD pada bayi tercapai. Kata Kunci: Inisiasi Menyusu Dini (IMD), Pengetahuan, Pendidikan dan Dukungan Suami